Examining the Turkish Century Education Model Preschool Education Program and the MoNE 2024 Preschool Education Program in the context of values education - Boz, Muhammed Emre; Akman, Berrin; Yazici, Dila Nur (Discover, 2026)
This study compares how values are made textually visible in two national preschool curriculum documents in Türkiye: the MoNE 2024 Preschool Education Program and the Turkish Century Education Model (TYMM) Preschool Education Program. Using qualitative document analysis, we conducted deductive values mapping in which each program’s stated value list and official value descriptions served as the analytic framework. For MoNE, the 12 values listed in the program text constituted the coding framework; for TYMM, the 20 values presented in Appendix 14 (Virtue-Value-Action tables) served as the primary analytic framework, as this appendix is the program’s principal document for defining and operationalising values. The unit of analysis was each learning outcome read together with its immediately related indicators, skills, and explanatory statements. Coding was conducted by the first author via hand coding, then refined through six consensus meetings with the co-authors and reviewed by one external expert. Descriptive indicators included total value links, links per outcome, and the proportion of outcomes linked to at least one value. The MoNE program (86 outcomes) yielded 174 value links (2.02 links per outcome) and 81.4% coverage (70 outcomes). The TYMM program (98 outcomes) yielded 144 links (1.47 links per outcome) and 69.4% coverage (68 outcomes). The two programs thus exhibit different patterns of value distribution across domains, reflecting their distinct curricular architectures rather than differences in educational quality. Findings should be interpreted as indicators of curricular explicitness and distribution in program texts, not as evidence of classroom implementation effectiveness. © The Author(s) 2026.
Keywords: Curriculum Mapping; Preschool Curriculum; Qualitative Document Analysis; Turkish Century Education Model; Values Education